Simultaneous Conference Interpreting and a Supernorm That Governs It All - Zwischenberger, Cornelia (Meta, 2015)
The integration of the concept of “social norm” into research on conference interpreting dates back to the late 1980s (Shlesinger 1989). This paper will show that conference interpreting is governed by role-related normative expectations which ultimately can all be traced back to the metaphoric concept of interpreters as conduits. This metaphoric concept that can be found in so many of the extratextual (re)sources on conference interpreting (Toury 1995) is extremely binding for conference interpreters and can therefore be regarded as an omnipotent norm – a supernorm that governs it all. Not only professional bodies such as the International Association of Conference Interpreters (AIIC), probably the most influential and powerful norm-setting authority in the field, but also individual authoritative personalities play a key role in promoting this supernorm. It is only in recent years that this supernorm, which demands that interpreters passively channel a message from one side or party to the other and thus tries to prevent an interpreter’s agency, has been challenged by empirical research (Angelelli 2004; Diriker 2004; Zwischenberger 2013). The discussion on norms in simultaneous conference interpreting will be enhanced by some selected findings of a web-based survey which was conducted among AIIC members. The survey’s main objective was to find out whether and to what degree professional conference interpreters adhere to the supernorm so strongly advocated by their professional body.